A Study on the Involvement of HRP in the Implementation of Lean Thinking Practices in IT Companies - B., Megha; Dath, T. N. Srikantha (Prabandhan: Indian Journal of Management, 2025)
Purpose : This study explored the impact of human resource practices (HRP) as the mediating or moderating variables in implementing lean thinking practices (LTP) in IT companies in India. The focus was to establish an association between LTP, HRP, and organization performance (OP) constructs. Design : Cross-sectional research was adopted, and a structured questionnaire was used to collect 528 responses from IT companies. Mediation analysis by SOBEL test and moderation analysis by multiple regression were used to establish an association between the constructs. Findings : The findings revealed that the interception of the HRP strengthened the association between LTP and OP as moderators, namely employee selection, rewards and recognition, human resource policies, procedures and benchmarking, training and development, and performance feedback. Practical Implications : This study provided inputs to managers, engineers, and HR policymakers for implementing LTP to enhance employee productivity, performance, and well-being through continuous improvement and collaboration. Originality : Substantial research on “Lean Thinking” and the need for “Human Resources (People)” in lean thinking implementation are available in the extant literature. However, effective HRPs and their impact on lean thinking implementation were less explored. Hence, this study provided a potential guide for IT practitioners adopting lean thinking.